The pure effect of social preferences on regional location choices: The evolving dynamics of convergence to a steady state population distribution. (11th April 2019) - Stark, Oded; Budzinski, Wiktor; Kosiorowski, Grzegorz
Abstract: This paper tracks the consequences of individuals' desire to align their location with their social preferences. The social preference studied in the paper is distaste for relative deprivation, measured in a cardinal manner. Location is conceived as social space, with individuals choosing to relocate if, as a result, their relative deprivation will be reduced, holding their incomes constant. Conditions are provided under which the associated dynamics reaches a spatial steady state, the number of periods it takes to reach a steady state is specified, and light is shed on the robustness of the steady state outcome. By way of simulation it is shown that for large populations, a steady state of the relocation dynamics is almost always reached, typically in one period, and that cycles are more likely to occur when the populations' income distributions are more equal.